Parenting Program for Kindergarten - Fadillah Fadillah; Purwanti Purwanti (JPKM (Jurnal Pengabdian Kepada Masyarakat) UNTAN, 2018)
Parenting programs in kindergartens are educational services carried out on parents' cooperation with the TK parties to stimulate youth development. The cooperation that is good for both parents, nurturing, educating, is indeed needed to grow. The collaboration model is called the parenting program. Given the importance of this parenting program, it is necessary to look at the dissemination of the parenting program aimed at the Head/Kindergarten Teachers by disseminating the parenting program in the form of a pocketbook which can be attended in the kindergarten library so that teachers read that the parenting program is not included and watching videos of parenting program implementation at TK PAUD institutions, and playing guessing is responsible for increasing understanding of parenting programs.